PENGARUH REMUNERASI, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI RSUD dr. FAUZIAH BIREUEN - Damayanti, Ina; Konadi; Mirja (LPPM-UNIKI, 2024)
Research was conducted to determine the influence of remuneration, work motivation and leadership style of Dr Fauziah Bireuen Hospital employees on employee performance. Based on survey research via questionnaires on a sample of 109 employees with quantitative analysis techniques using multiple regression. The research results show that remuneration influences the performance of RSUD dr. Fauziah Bireuen. Work motivation influences employee performance and leadership style influences employee performance. Simultaneously, remuneration, work motivation and leadership style influence Dr. Fauziah Bireuen amounted to 25.745%.